Health policy under the microscope: a micro policy design perspective - Capano, Giliberto; Toth, Federico (Frontiers in Public Health, 2023)
The comparative study of health policy has focused mainly on the macro-structural dimensions of health systems and reforms that have sought to change these organizational arrangements. Thus, a great deal of attention has been paid to the multiple models of insurance against sickness risks and various modes of organizing and financing healthcare providers. However, little attention has been paid to policy tools and policy design in the health policy domain. This research gap largely impedes a focus on the micro (granular) dimension of health policy, although this is the level at which health policies impact reality and thus deliver progress toward the expected goals. Such a focus on the micro dimension could not only allow a finer-grained comparison of how health systems work but also shed light on how capable health policies are of achieving the expected outcomes. This paper fills this gap by presenting an analytical framework capable of illuminating the granular dimension of policy design (the instrumental delivery package) and shows the analytical relevance of the framework by applying it to the designs of maximum waiting time guarantee and vaccination mandate policies.